Perancangan Ulang Tata Letak Fasilitas Untuk Meminimasi Ongkos Material Handling - Wahyuniardi, Rizki; Setiawan, Agi (Performa: Media Ilmiah Teknik Industri, 2014)
PT. Kirana Semesta Panganis a company engaged in the field of food processing. The industry isproducing a wide range of food products such as meatballs, spicy meatballs and sauce seasoning. From the initial identification, the existing conditions of production layout does not fit the flow of the production process, thus causing the material handling is not optimal. The purpose of this research is to improve the plant layout to minimize the cost of material handling using Systematic Layout Planning (SLP). This research is obtained 3 alternatives layout that is able to minimize the cost of material handling by 24,15-36,41%. With this result, the company can choose the layout that fits the production process.